Simbol Cinta Manusia dalam Novel Zuhūr Taʾkuluhā Al-Nār Karya Amir Tag Elsir : (Semiotika Charles Sanders Pierce) - Nurhitjah Rambe; Maman Abdul Jalil; Wildan Taufiq (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Love is an inseparable part of human life, because humans will always need love in any case to continue life, because love is human nature. The intensity of love felt will vary, depending on the person who feels it and to whom the love is. Functions as a source of positive energy but can also cause bad things if misunderstood. This research aims to understand the semiosis of love symbols in the novel "Zuhūr Taʾkuluhā al-Nār" by Amir Tag Elsir using Charles Sanders Peirce's semiotic approach. This research connects the results with Sternberg's love triangle theory. The method used is analytical descriptive qualitative research. The research results identified 25 data that reflect six love symbols: liking, infatuation love, empty love, romantic love, companionate love, and fatuous love.